Wettability measurement under high P‐T conditions using X‐ray imaging with application to the brine‐supercritical CO2 system. (30th August 2015) - Chaudhary, Kuldeep; Guiltinan, Eric J.; Cardenas, M. Bayani; Maisano, Jessica A.; Ketcham, Richard A.; Bennett, Philip C.
Abstract We present a new method for measuring wettability or contact angle of minerals at reservoir pressure‐temperature conditions using high‐resolution X‐ray computed tomography (HRXCT) and radiography. In this method, a capillary or a narrow slot is constructed from a mineral or a rock sample of interest wherein two fluids are allowed to form an interface that is imaged using X‐rays. After some validation measurements at room pressure‐temperature conditions, we illustrate this method by measuring the contact angle of CO2‐brine on quartz, muscovite, shale, borosilicate glass, polytetrafluoroethylene (PTFE or Teflon), and polyether ether ketone (PEEK) surfaces at 60–71°C and 13.8–22.8 MPa. At reservoir conditions, PTFE and PEEK surfaces were found to be CO2‐wet with contact angles of 140° and 127°, respectively. Quartz and muscovite were found to be water‐wet with contact angles of 26° and 58°, respectively, under similar conditions. Borosilicate glass‐air‐brine at room conditions showed strong water‐wet characteristics with a contact angle of 9°, whereas borosilicate glass‐CO2‐brine at 13.8 MPa and 60°C showed a decrease in its water‐wetness with contact angle of 54°. This method provides a new application for X‐ray imaging and an alternative to other methods.